Surveys of waterbirds in the Darkhad Depression, Mongolia, during summer and autumn - Call, Mikayla N.; Schummer, Michael L.; Smith, Chris J.; Dovchin, Badamgarav; Tumur, Battagtoh; Byambaa, Bayarkhuu; Jal, Tumurusukh; Watters, Rebecca J. (Wildfowl, 2019)
The Darkhad Depression provides one of the most extensive concentrations of waterbird breeding, moulting, and migration stopover site habitat in Mongolia. To our knowledge, this is the first large-spatial scale survey completed for waterbirds in the region. Surveys were conducted at 60 wetlands and a portion of a river (total area = 5,873 ha) in summer (15−19 July), and at 36 wetlands (5,285 ha, including 27 wetlands from the summer) in autumn 2018 (6−10 October). Thirty-seven species were detected (13 with juveniles) during the summer and 23 species in autumn. The frequency of occurrence of species among wetlands and densities of waterbirds among occupied wetlands (birds/ha) were calculated for summer. These estimates were scaled to the total wetland area in the region, for estimating the proportion of the flyway population occurring in the Darkhad Depression for each species. Six species were on the IUCN Red List (IUCN 2018) or in the Mongolian Red Book (Shiirevdamba et al. 2016): Falcated Duck Anas falcata, Common Pochard Aythya ferina, Common Crane Grus grus, Northern Lapwing Vanellus vanellus, Eurasian Curlew Numenius arquata, and Horned Grebe Podiceps auritus. In summer, Common Goldeneye Bucephala clangula used the greatest percentage of wetlands included in the survey (57.4%) and Tufted Duck Aythya fuligula had the greatest mean density among occupied wetlands (6.66 ± 5.69 s.e. birds/ha). Most individuals appeared to be moulting adults. Greatest juvenile:adult ratios were for Eared Grebes Podiceps nigricollis (1.3), Ruddy Shelduck Tadorna ferruginea (1.4), and Whooper Swans Cygnus cygnus(1.1). In autumn, Common Goldeneye (n = 1,375), dabbling ducks (Anas sp.; n = 2,206), and Whooper Swans (n = 1,065) were the most common waterbirds observed, and 88% of all waterbirds counted occurred on just three wetlands. The Darkhad Depression appears to be important for waterbirds from the Central and East Asian Flyways, and our surveys suggest it likely supports > 1% of Common Goldeneye, Tufted Duck, Bar-headed Goose Anser indicus, and Ruddy Shelduck populations of these Flyways. To develop a greater understanding of waterbird reproduction and seasonal use, as well as threats to waterbirds in the region, we suggest that standardised surveys should be undertaken during spring through to autumn in future years.